Processed meat, red meat, white meat, and digestive tract cancers: A two-sample Mendelian randomization study - Yun, Zhangjun; Nan, Mengdie; Li, Xiao; Liu, Zhu; Xu, Jing; Du, Xiaofeng; Dong, Qing; Hou, Li (Frontiers in Nutrition, 2023)
Background: Previous observational studies suggested inconsistent insights on the associations between meat intake and the risk of digestive tract cancers (DCTs). The causal effect of meat intake on DCTs is unclear. Methods: Two-sample Mendelian randomization (MR) was performed based on genome-wide association studies (GWAS) summary data from UK Biobank and FinnGen to evaluate the causal effect of meat intake (processed meat, red meat (pork, beef, lamb), white meat (poultry)) on DCTs (esophageal, stomach, liver, biliary tract, pancreatic and colorectal cancers). The estimates of causal effects are based on primary analysis inverse-variance weighted (IVW) and complementary analysis MR-Egger, weighted median. Sensitivity analysis using Cochran Q statistic, funnel pot, MR-Egger intercept, and leave-one-out. MR-PRESSO and Radial MR are performed to identify and remove outliers. Multivariable MR (MVMR) was used to demonstrate direct causal effects. Risk factors were introduced to explore potential mediators of exposure and outcome. Results: The estimates of univariable MR analysis supported that genetically proxied processed meat intake increased the risk of colorectal cancer (IVW: (odds ratio (OR) = 2.12, 95% confidence interval (CI) 1.07–4.19; P = 0.031). The causal effect is consistent in MVMR (OR = 3.85, 95% CI 1.14–13.04; P = 0.030) after controlling for the influence of other exposures. The causal effects described above were not mediated by body mass index and total cholesterol. There was no evidence to support the causal effects of processed meat intake on other cancers except colorectal cancer. Similarly, no causal association between red meat, white meat intake, and DCTs. Conclusions: Our study reported that processed meat intake increases the risk of colorectal cancer rather than the other DCTs. No causal relationship was observed between red and white meat intake and DCTs.